(untitled) (Iranian Journal of Kidney Diseases, 2017)
Aspartame is one of the most popular artificial sweeteners over the world. Although its consumption is considered to be safe in acceptable daily intake ranges which were set by the United States Food and Drugs Administration and other regulatory agencies, there are lots of controversies regarding its safety nowadays. Some of the recent experimental and epidemiological studies showed that consumption of aspartame may causes some adverse health effects including obesity, metabolic syndrome, and alteration in gut microbiota. Moreover, studies on the nephrotoxic effect of aspartame have increased. A search of several literature databases for publications on adverse effects of aspartame on the kidney function from 1980 to 2016 showed that long-term consumption of aspartame led to a dose-dependent increased production of free radicals in renal tissues as well as kidney injury, based on several studies on animals However, given the lack of clinical data in this area, it is difficult to make a definitive conclusion regarding nephrotoxic effect of aspartame. Overall, consumers should be aware of the potential side effects of aspartame and other artificial sweeteners. At present it may be recommended that only a minimal amount of them would be consumed.